Reframing informal tourism entrepreneurial practices: capital and field relations structuring the informal tourism economy of Chiang Mai - Çakmak, Erdinç; Lie, Rico; McCabe, Scott (Elsevier, 2018)
This article examines the types of capitals possessed by informal tourism entrepreneurs and locates their value within the field relations that orders their contribution to the tourism system. Bourdieu’s theory on fields and capitals was applied to ethnographic narrative accounts of stakeholders in tourism in Chiang Mai, Thailand to assess these roles. Informal entrepreneurs have limited access to resources and their perspectives are excluded from academic debates and policy initiatives. The paper identifies the dynamism, positive social capital, flexibility, and symbolic capital of informal entrepreneurs. These are related to the field conditions that determine and structure their contribution to tourism destinations. The analysis reveals the importance of collaboration between informal entrepreneurs and other stakeholders, concluding with recommendations for policy makers.